Development of instrumented downhill bicycle components for field data collection - Petrone, N.; Giubilato, F.; Giro, A.; Mutinelli, N. (Procedia Engineering, 2012)
A downhill bicycle was equipped with strain gauge bridges at the most significant safety components, stroke sensors at the suspensions and accelerometers at the front axle. A set of 7 channels was applied on the frame, 4 channels were applied to the rear swing arm, 6 channels to the front fork, 2 channels to the front and rear brakes and a customized load cell was connected to the rear damper. Each channel was calibrated during static laboratory tests and the calibration constants or matrices were used to convert the measured signals into functional loads applied to the components. Tests were performed involving an expert downhill racer on a competition track. The peak values collected during the study would allow for the definition of static overload tests on the bicycle safety components; the time histories collected in the field will allow evaluating the field loads spectra to be used in the fatigue life prediction of the components and defining the standard fatigue tests to verify the minimum required fatigue strength of the most important components of such an extreme sport discipline.